Machiavellian Privatization - Biais, Bruno; Perotti, Enrico (American Economic Review, 2002)
We analyze politically motivated privatization in a bipartisan environment. When median-class voters a priori favor redistributive policies, a strategic privatization program allocating them enough shares can induce a voting shift away from left-wing parties whose policy would reduce the value of shareholdings. To induce median-class voters to buy enough shares to shift political preferences, strategic rationing and underpricing is often necessary. In the extreme, this may lead to free share distribution and voucher privatization. Shifting voting preferences becomes impossible when strong ex ante political constraints require large upfront transfers to insiders or when social inequality is extreme.